Modulation of Gonadotropins Activity by Antibodies - Kara, Elodie; Dupuy, Laurence; Bouillon, Céline; Casteret, Sophie; Maurel, Marie-Christine (Frontiers in Endocrinology, 2019)
Gonadotropins are essential for reproduction control in humans as well as in animals. They are widely used all over the world for ovarian stimulation in women, spermatogenesis stimulation in men, and ovulation induction and superovulation in animals. Despite the availability of many different preparations, all are made of the native hormones. Having different ligands with a wide activity range for a given receptor helps better understand its molecular and cellular signaling mechanisms as well as its physiological functions, and thus helps the development of more specific and adapted medicines. One way to control the gonadotropins' activity could be the use of modulating antibodies. Antibodies are powerful tools that were largely used to decipher gonadotropins actions and they have shown their utility as therapeutics in several other indications such as cancer. In this review, we summarize the inhibitory and potentiating antibodies to gonadotropins, and their potential therapeutic applications.